Folate pathway genes linked to mitochondrial biogenesis and respiration are associated with outcome of patients with stage III colorectal cancer - Elisabeth Odin; Arvid Sondén; Göran Carlsson; Bengt Gustavsson; Yvonne Wettergren (Tumor Biology)
5-fluorouracil in combination with the folate leucovorin is the cornerstone in treatment of colorectal cancer. Transport of leucovorin into cells, and subsequent metabolic action, require expression of several genes. The aim was to analyze if tumoral expression of genes putatively involved in leucovorin transport, polyglutamation, or metabolism was associated with outcome of patients with stage III colorectal cancer treated with adjuvant chemotherapy. A total of 363 stage III colorectal cancer patients who received adjuvant bolus 5-fluorouracil + leucovorin alone, or in combination with oxaliplatin according to Nordic bolus regimes were included. Expression of 11 folate pathway genes was determined in tumors using quantitative real-time polymerase chain reaction and related to disease-free survival. The median follow-up time was 5 years. During follow-up, 114 (31%) patients suffered from recurrent disease. A high tumoral expression of the genes SLC46A1/PCFT, SLC19A1/RFC-1, ABCC3/MRP3, GGH , and MTHFD1L , which are involved in folate transport, polyglutamation, or metabolism, was associated with longer disease-free survival of the patients. Each of these genes either encodes mitochondrial enzymes or is being regulated by mitochondrial transcription factors. Expression of the SLC46A1/PCFT gene was most strongly associated with disease-free survival, regardless of treatment regimen. In conclusion, the results show that expression of folate pathway genes are associated with outcome of colorectal cancer patients treated with adjuvant 5-fluorouracil in combination with leucovorin. A prospective study needs to be conducted to determine if expression of these genes can be used to predict response to leucovorin and other folates that are now being tested in clinical studies. Moreover, there seems to be a link between folate metabolism and mitochondrial biogenesis and respiration that deserves further exploration.